1992
DOI: 10.1007/bf00443476
|View full text |Cite
|
Sign up to set email alerts
|

Cementless prosthesis of the hip joint with ?spongy metal? surface

Abstract: Our investigations in human specimens and animal experiments show that prostheses with a spongy metal surface can become fixed by bony ingrowth to varying degrees. After consistent clinical and radiological follow-up over 12-65 months (mean 34 months) in a prospective study of 100 consecutive patients in whom 106 cementless total hip replacements had been carried out, we were able to show that after 1 year 82% of patients were pain-free with the prosthesis fixed by bony ingrowth, 8% were pain-free with the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Bone ingrowth into the metal-cancellous structure of the MCCL prosthesis has been demonstrated in animal experiments and by examination of specimens retrieved from patients [25,26]. The good radiological results in our series with no aseptic loosening suggest that bone ingrowth may prevent amyloid deposition at the implant-bone interface, which is thought to be one of the causes of aseptic loosening.…”
Section: Discussionsupporting
confidence: 51%
“…Bone ingrowth into the metal-cancellous structure of the MCCL prosthesis has been demonstrated in animal experiments and by examination of specimens retrieved from patients [25,26]. The good radiological results in our series with no aseptic loosening suggest that bone ingrowth may prevent amyloid deposition at the implant-bone interface, which is thought to be one of the causes of aseptic loosening.…”
Section: Discussionsupporting
confidence: 51%
“…A 3-year prospective randomized trial that examined the prognostic value of osteoporosis in terms of implant failure indicated that 76% of failures occurred in osteoporotic patients (2). When cementless hip replacements were evaluated in 106 consecutive implants, the high success led to the reserved suggestion that a cementless prosthesis should be implanted only in patients without osteoporosis (35). Upon revision of 175 cementless porous coated prostheses, the observation of severe stress shielding (peri-implant bone loss of biomechanical etiology) was correlated with pre-operative osteoporosis (30).…”
Section: Fig 3 Decreasing Bone Density Is Associated With Decreas-mmentioning
confidence: 99%
“…Bone ingrowth into the metal-cancellous structure has been demonstrated in animal experiments and in studies of specimens retrieved from patients. 13,14 Initial stability of the metal socket is achieved by two spikes wedged into the anterior and posterior parts of the acetabular rim, and a peg embedded into the ischium. The polyethylene liner is inserted during the operation, and has a 10° wedge-shaped overhang to increase superolateral coverage.…”
Section: Methodsmentioning
confidence: 99%
“…The Metal-Cancellous Cementless Lübeck (MCCL) prosthesis (S&G; ESKA, Lübeck, Germany) was developed with these aims and has been used in Europe and Japan, but only short-term results have been published. [12][13][14] We now report our intermediate-term clinical and radiological results.…”
mentioning
confidence: 99%